2009
DOI: 10.1016/j.jpainsymman.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to and Lessons Learned from Conducting Palliative Care Research

Abstract: In response to a 2005 NIH solicitation, sixteen investigators received funding to test interventions that would reduce the barriers that prevent cancer patients from receiving adequate and appropriate symptom management therapies. Since the awards have been issued, the investigators have met two times and have identified a number of challenges to implementing their respective studies. A survey was conducted that focused on their experiences with hiring and retaining study personnel, gaining Institutional Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 4 publications
3
43
0
1
Order By: Relevance
“…But it supports the findings of other studies that limited physical and emotional resources result in lower study participation [5]. This of course applies to all research but is a point especially relevant to research in palliative care [2,9,10].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…But it supports the findings of other studies that limited physical and emotional resources result in lower study participation [5]. This of course applies to all research but is a point especially relevant to research in palliative care [2,9,10].…”
Section: Discussionsupporting
confidence: 84%
“…The barriers for end-of-life research compare well to international experience [5,10]. In the US experience with SAHD, a minority of 22% of all admitted patients could be assessed [1].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our study offered teaching credits and financial incentives to PCPs recruiting patients. 11 Although the difficulty of conducting research in patients who require PC has been widely acknowledged, with losses up to 60%, 24 patients show a high tendency to take part in noninvasive studies, mainly focused on symptom control and QOL; they are willing to complete questionnaires, and are more likely to get involved if their physician and caregiver are also involved in the research. 25,26 The advantages of using online training over the traditional lecture format are: active learner involvement, flexibility, interaction and dissemination capabilities, learner satisfaction, and reduced cost.…”
Section: Discussionmentioning
confidence: 99%
“…Issues affecting research include the difficulties in recruiting and retaining participants and the challenges in gaining ethical approval. 37 The studies on caring and post-bereavement distress have tended to overlook that, as a consequence of caring for a dying loved one, family caregivers may be highly distressed upon bereavement.Thus, even if a former caregiver's distress decreases over time, it cannot necessarily be concluded that this is a return to 'normal. '…”
mentioning
confidence: 99%